Quantum dot tracing slow-release proppant and preparation method thereof
By using quantum dot traced sustained release proppants in oil field development, the problem of poor stability of ordinary proppants in high temperature and high pressure environments is solved, better crack support and monitoring effects are achieved, and the stability and production efficiency of the oil field are improved.
Patent Information
- Application Number
- CN202510044601.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-12
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, ordinary proppants have poor stability in high temperature and high pressure environments and cannot sustain cracks, which limits the effectiveness and economic benefits of oil field development.
The quantum dot tracer sustained release proppant was prepared by solvent evaporation. By mixing silicon-based quantum dot tracer, ceramide proppant and polyamide methacrylate in the polymer solution, a proppant with strong fluorescence characteristics and good stability was formed.
Quantum dot tracer sustained release proppants show good durability and flow diversion ability in high temperature and high pressure environments, and can monitor the crack status in a long time and meet the needs of oil fields to stabilize oil production.
Smart Images

Figure BDA0005237999130000051 
Figure BDA0005237999130000052 
Figure BDA0005237999130000053
Abstract
Description
Technical Field
[0001] The invention relates to the field of oil production engineering technology and fracturing technology, and in particular to a method for preparing a quantum dot tracer slow-release proppant. Background Art
[0002] At present, most of the domestic oil fields in my country have entered the middle and late stages of development. The comprehensive water content of the oil fields has increased year by year, and the difficulty of increasing and stabilizing production has gradually increased. Unconventional oil and gas resources with large geological reserves are currently attracting much attention. In particular, unconventional resources represented by tight oil have received increasing attention from all walks of life. Tight oil and gas reservoirs are a new field in the petroleum industry and are very important unconventional oil and gas resources in the world. However, due to the poor reservoir conditions and low permeability and porosity of tight oil reservoirs, in order to obtain higher production capacity in oil field development, oil well fracturing technology has been continuously developed, especially horizontal well fracturing technology has become the main means of effectively developing tight oil. Among them, proppant plays an important role in the fracturing process and is related to the diversion effect of the propped fracture.
[0003] However, the detailed description of the fracture network structure formed after fracturing has become a difficult problem in the development of tight oil reservoirs and even other unconventional oil and gas resources, which determines the accuracy of the effect evaluation and production dynamic prediction after fracturing. Ordinary proppants may break under high temperature and high pressure environment, resulting in the inability of fractures to open continuously. Especially in deep oil and gas reservoirs, ordinary proppants have poor stability and may deform or lose, which greatly limits their application. Therefore, in many high-demand oil and gas fields, in order to improve the fracturing effect and economic benefits, more professional and high-performance proppants are usually required, such as ceramsite proppants, coating proppants, etc. These proppants have better strength, high temperature resistance and durability. Therefore, there is an urgent need for a high-performance proppant with low dosage, low cost, good stability, and high performance, which can effectively describe the fracture network structure and morphology after fracturing, facilitate the evaluation of fracturing effect, and meet the needs of oilfields for stable oil production and increased production. Summary of the invention
[0004] In response to the above problems, the present invention provides a method for preparing a quantum dot tracer slow-release proppant, which is used to solve the problems existing in the prior art, such as poor stability of ordinary proppants and inability to continuously support cracks in high temperature and high pressure environments.
[0005] The invention provides a method for preparing a quantum dot tracer slow-release proppant, which uses ceramsite proppant, polymethacrylate and acetone as raw materials and adopts a solvent evaporation method to prepare the quantum dot tracer slow-release proppant.
[0006] The preparation method of the quantum dot tracer slow-release proppant comprises the following steps:
[0007] S1: First, take a certain amount of silicon-based quantum dot tracer and add it to the acetone solution and stir it thoroughly;
[0008] S2: then adding polymethacrylate to the solution containing the acetone solution and the silicon-based quantum dot tracer, and continuing to stir until the polymethacrylate is completely dissolved;
[0009] S3: adding a certain amount of ceramsite proppant into a mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer;
[0010] S4: Then, the ceramsite proppant coated with the polymer solution in S3 is placed in a drying oven and evaporated for a period of time;
[0011] S5: Finally, the dried ceramsite proppant is placed in a certain amount of deionized water, and the quantum dot slow-release proppant is obtained after ultrasonic dispersion for a period of time.
[0012] In the preparation method of the quantum dot tracer slow-release proppant, a certain amount of silicon-based quantum dot tracer is taken, added to a certain amount of acetone solution and stirred thoroughly. In the step, 2 ml of silicon-based quantum dot tracer is taken, added to 4 ml of acetone solution and stirred thoroughly.
[0013] In the preparation method of the quantum dot tracer slow-release proppant, polymethacrylate is added to a solution containing an acetone solution and a silicon-based quantum dot tracer, and stirring is continued until the polymethacrylate is completely dissolved. In the step, 1.2 ml of polymethacrylate is added to the solution containing an acetone solution and a silicon-based quantum dot tracer, and stirring is continued for 20 minutes until the polymethacrylate is completely dissolved.
[0014] In the preparation method of quantum dot tracer slow-release proppant, a certain amount of ceramsite proppant is added into a mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer, and 10g of ceramsite proppant is added into the mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer.
[0015] In the preparation method of quantum dot tracer slow-release proppant, the ceramsite proppant wrapped by the polymer solution in S3 is placed in a drying oven and evaporated for a period of time. In the step, the ceramsite proppant wrapped by the polymer solution is placed in a drying oven at 120° C. and evaporated for 3 hours.
[0016] In the preparation method of quantum dot tracer slow-release proppant, the dried ceramsite proppant is placed in a certain amount of deionized water, and ultrasonically dispersed for a period of time to obtain the quantum dot slow-release proppant. In the step of drying, the dried ceramsite proppant is placed in 50 ml of pure water, and ultrasonically dispersed for 30 minutes to finally obtain the quantum dot slow-release proppant.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The quantum dot tracer slow-release proppant of the present invention is mainly obtained by mixing a quantum dot tracer and a ceramsite proppant in a polymer solution, wherein the quantum dot tracer has a strong and stable fluorescence characteristic, so the quantum dot slow-release proppant is injected into the formation along with the fracturing fluid, and the flowback fluid can be measured by fluorescence spectroscopy to determine the fracture state. Therefore, the quantum dot slow-release proppant of the present invention can be used for monitoring the fracturing cracks on the spot in the oil field, and has the advantages of being environmentally friendly, capable of long-term real-time monitoring, good high temperature resistance and durability, etc.
[0019] 2. The quantum dot tracer slow-release proppant of the present invention has a simple synthesis method and low synthesis cost, is conducive to the use of on-site oil fields, can meet the needs of accurate identification of fracture structures, is conducive to real-time evaluation of fracturing effects, and lays a theoretical foundation for oil and gas field development. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art description are briefly introduced below. Obviously, the drawings described below are only drawings required for use in some embodiments of the present invention or the prior art description. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work, and they all belong to the protection scope of the present invention.
[0021] Figure 1 This is a flow chart of a method for preparing a quantum dot tracer slow-release proppant according to an embodiment of the present invention;
[0022] Figure 2 This is a scanning electron microscope image of a quantum dot tracer slow-release proppant according to an embodiment of the present invention;
[0023] Figure 3 This is a finished product picture of a quantum dot tracer slow-release proppant under ultraviolet light according to an embodiment of the present invention;
[0024] Figure 4 This is the effect of the amount of polymer solution on the solubility of quantum dot tracer slow-release proppant;
[0025] Figure 5 This is a graph showing the effect of the amount of polymer solution on the apparent density of quantum dot tracer slow-release proppant;
[0026] Figure 6 This is the effect of solvent type on the solubility of quantum dot tracer slow-release proppant;
[0027] Figure 7 This is a diagram showing the effect of solvent type on the apparent density of quantum dot tracer slow-release proppant;
[0028] Figure 8 It is a curve diagram showing the change of conductivity of common proppant and quantum dot tracer slow-release proppant with effective closure pressure;
[0029] Fig. 9 It is a curve diagram of cumulative release concentration of quantum dot tracer slow-release proppant;
[0030] Fig.10 This is a graph showing the effect of temperature on the release rate of quantum dot tracer slow-release proppants;
[0031] Fig.11 This is a graph showing the effect of mineralization on the release rate of quantum dot tracer slow-release proppant;
[0032] Fig.12 This is a graph showing the effect of flow rate on the release rate of quantum dot tracer slow-release proppant. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The present invention will be further described below with reference to specific embodiments and accompanying drawings:
[0035] The invention provides a method for preparing a quantum dot tracer slow-release proppant, which uses ceramsite proppant, polymethacrylate and acetone as raw materials and adopts a solvent evaporation method to prepare the quantum dot tracer slow-release proppant. The method for preparing the quantum dot tracer slow-release proppant comprises the following steps:
[0036] S1: First, take a certain amount of silicon-based quantum dot tracer and add it to the acetone solution and stir it thoroughly;
[0037] S2: then adding polymethacrylate to the solution containing the acetone solution and the silicon-based quantum dot tracer, and continuing to stir until the polymethacrylate is completely dissolved;
[0038] S3: adding the ceramsite proppant into a mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer;
[0039] S4: Then, the ceramsite proppant coated with the polymer solution in S3 is placed in a drying oven and evaporated for a period of time;
[0040] S5: Finally, the dried ceramsite proppant is placed in deionized water, and the quantum dot slow-release proppant is obtained after ultrasonic dispersion for a period of time.
[0041] The specific preparation process is as follows Figure 1 As shown, first, a certain amount of silicon-based quantum dot tracer is taken and added to an acetone solution and stirred evenly; then polymethacrylate is added to the solution containing the acetone solution and the silicon-based quantum dot tracer, and stirring is continued until the polymethacrylate is completely dissolved; then ceramsite proppant is added to the mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer; then the ceramsite proppant wrapped by the polymer solution in S3 is placed in a drying oven and evaporated for a period of time; finally, the dried ceramsite proppant is placed in deionized water, and the quantum dot slow-release proppant is obtained after ultrasonic dispersion for a period of time.
[0042] Figure 2 This is a scanning electron microscope image of a quantum dot tracer slow-release proppant. The image was magnified 1,000,000 times using a FEIQuanta 650FEG field emission scanning electron microscope produced by Thermo Fisher Scientific. The successful coating of the spherical quantum dot slow-release proppant can be clearly seen in the image.
[0043] Figure 3 This is a finished picture of a quantum dot tracer slow-release proppant under ultraviolet light. From the picture, it can be seen that the expanded clay proppant is wrapped by the quantum dot tracer and has strong fluorescence.
[0044] Example 1 is a quantum dot tracer slow-release proppant volume density and crushability test experiment, which specifically includes the following steps:
[0045] (1) Bulk density test method
[0046] The proppant breakage rate tester was used to test the breakage rate of the proppant. The test method of the proppant bulk density is as follows: first, weigh the mass m1 of the dry density bottle, and fill the density bottle with low-viscosity test liquid to record the mass as m2; then fill the dried density bottle with proppant mass m3, and the density of the test liquid is ρ; finally, put the proppant sample into the density bottle.
[0047] Bulk density calculation formula:
[0048]
[0049] Where: b —Volume density g / cm 3 ; m1-mass of density bottle, g; m2-mass of density bottle filled with test fluid, g; m3-mass of density bottle filled with proppant, g; ρ-density of test fluid, g / cm 3 .
[0050] The method for measuring apparent density is to first weigh the mass of the dry density bottle, then fill the density bottle with test liquid at ambient temperature (no bubbles should exist in the density bottle), wipe the density bottle dry and weigh the mass of the density bottle containing the test liquid, add the accurately weighed proppant sample into the density bottle and fill it with test liquid, and finally measure the mass of the density bottle containing the proppant and test liquid to calculate the apparent density of the sample.
[0051] The formula for calculating apparent density is:
[0052]
[0053] Where: s -Apparent density g / cm 3 ; m4 - sample mass g; m5 - the combined mass of the density bottle and the test liquid g; m6 - the combined mass of the sample, density bottle and test liquid g; ρ - the density of the test liquid g / cm 3 .
[0054] (2) Breakage rate test method
[0055] First, prepare the sample to be tested, and calculate the mass of the sample to be tested by measuring its volume density; m p =24.7ρ b (m p is the calculated mass of the sample to be tested, g; ρ b is the bulk density of the sample, g / cm 3 ). Then start the proppant breakage rate test equipment, check the status of the oil pump and compensation pump, and use a balance to weigh the proppant sample (not more than 5g of the calculated mass of the sample to be tested), recorded as m s , close the oil return valve of the hydraulic press, open the oil supply valve, run the control software, add the rated load to the crushing chamber at a uniform speed within 1 minute, and unload after 2 minutes of stable load; finally weigh the mass of the crushed particles in the chassis, recorded as m pan , the crushing rate of the proppant sample is calculated according to the formula;
[0056]
[0057] Where: m' pan is the proppant breakage rate, %; m pan is the mass of particles produced in the experiment, g; m s is the mass of proppant placed in the crushing chamber, g.
[0058] Table 1 is the volume density and crushing pressure test data of the quantum dot tracer slow-release proppant prepared in Example 1:
[0059]
[0060] As shown in Table 1, the volume density of the prepared quantum dot tracer slow-release proppant is between 1.25 and 1.56 g / cm 3 The breakage rate is between 4 and 9, both of which are lower than the standard requirements.
[0061] Example 2 is an experiment on the effect of the amount of polymer solution on the acid solubility and apparent density of quantum dot tracer slow-release tracer proppants. Take 50g of ceramsite proppant and place it in 6mL, 8mL, 10mL, 12mL, 14mL, 16mL, and 18mL of polymer solution (solution concentration is 10%) and stir it thoroughly. After the solvent evaporates completely, the proppant in the remaining solution is separated and sieved. The acid solubility and apparent density performance tests of the synthetic slow-release tracer proppant samples are performed. The performance test results are shown in Figure 4-5 .
[0062] It can be seen from the figure that the apparent density of the quantum dot tracer slow-release tracer proppant decreases with the increase of the polymer dosage; the acid solubility of the quantum dot tracer slow-release proppant shows a trend of first decreasing and then increasing in polymer solutions with different dosages.
[0063] Example 3 is an experiment on the effect of solvent type on the acid solubility and apparent density of quantum dot tracer slow-release tracer proppants, in order to better study whether the different types of solvents used in the synthesized slow-release tracer proppants will affect the properties of the product. Methanol, ethanol, acetone, isopropanol and acetonitrile were used as solvents to prepare polymer solutions, and the concentration of the prepared polymers was 10%. Five proppant samples were synthesized with a ratio of 50g ceramsite to 10mL polymer solution, and the rest of the synthesis methods remained the same. The acid solubility and apparent density performance of the samples were also tested, and the performance test results are shown in Figure 6 and Figure 7 .
[0064] As can be seen from the figure, the apparent density of quantum dot tracer slow-release proppants synthesized using different types of solvents is basically the same, which shows that different solvents can form a polymer coating on the surface of the expanded clay proppant; when methanol, ethanol and acetone are used as solvents, the acid solubility of the synthesized quantum dot tracer slow-release proppants is not much different.
[0065] Example 4 is a test experiment of the conductivity of quantum dot tracer sustained-release tracer support, and the specific steps are as follows:
[0066] The experimental conditions were set as follows: 20 / 40 mesh proppant, sand concentration of 8 kg / m2, closure pressure between 6.9 MPa and 69 MPa, and flow rate of 3 mL / min. The conductivity of expanded clay and quantum dot tracer slow-release proppant was measured using an FCS-842 conductivity tester.
[0067] Figure 8This is a curve diagram of the change of conductivity of ordinary proppant and quantum dot tracer slow-release proppant with effective closure pressure in the experiment of Example 4: By comparing the ordinary proppant and the quantum dot tracer slow-release proppant in the process of changing the effective closure pressure from 5Mpa to 50Mpa, it can be seen that with the increase of the effective closure pressure, the conductivity of the two proppants decreases, but the conductivity of the quantum dot tracer slow-release proppant is slightly higher than that of the ordinary proppant, and when the effective closure pressure is greater than 10Mpa, the conductivity of the quantum dot slow-release tracer proppant remains good.
[0068] Example 5 is a quantum dot tracer slow-release proppant performance evaluation experiment, and the specific experimental method is as follows:
[0069] Add the prepared quantum dot tracer slow-release proppant into a beaker filled with water or kerosene, and maintain the same experimental conditions to allow the slow-release tracer proppant to be fully released, and take samples regularly, taking 3 ml of each sample. After sampling, continue to fill the liquid in the beaker to the initial volume.
[0070] Table 2 Experimental scheme for evaluating the performance of the quantum dot slow-release proppant prepared in Example 5:
[0071]
[0072] Example 5 Experimental results are as follows Fig. 9 As shown in the cumulative release concentration curve of the quantum dot tracer slow-release proppant, it can be seen that the release rate of the quantum dot tracer slow-release proppant is faster in the initial contact with the fluid, and the release rate gradually slows down until it stabilizes as time goes by.
[0073] Example 6 is an experiment on the effect of temperature on the release rate of quantum dot tracer slow-release proppant, which explores the effect of temperature in the range of 20°C to 90°C on the release rate of tracer slow-release proppant. Fig.10 These are the experimental results of the effects of different temperature conditions on the slow-release performance of quantum dot tracer slow-release proppants.
[0074] It can be seen from the figure that the increase in temperature is conducive to the release of silicon-based quantum dot tracers in quantum dot tracer slow-release proppants, and the release of tracers tends to be stable as the release time increases. The cumulative release concentration of the tracer is the largest at 80℃-90℃, and the maximum release rate is 35ppb. The cumulative release concentration of the tracer at 20℃-40℃ is close to coincident, and the release rate after stabilization is 7.5ppb, indicating that the release rate of the tracer is less affected under this temperature condition, and the release is slow at lower temperatures.
[0075] Example 7 is an experiment on the effect of mineralization on the release rate of quantum dot tracer slow-release proppant, which explores the effect of different mineralization on the release rate of tracer slow-release proppant. The results are as follows: Fig.11 shown.
[0076] From the figure showing the effect of mineralization on the release rate of quantum dot tracer slow-release proppant, it can be seen that with the increase of mineralization, the cumulative release concentration of the tracer slow-release proppant decreases. When the mineralization range is between 5000-10000 mg / L, it is conducive to the release of the tracer, while when the mineralization is greater than 20000 mg / L, it has a certain inhibitory effect on the release of the tracer.
[0077] Example 8 is an experiment on the effect of flow rate on the release rate of quantum dot tracer slow-release proppant. The quantum dot slow-release proppant has different flow rates in each section when it contacts the target fluid at different positions in the formation. Therefore, whether the difference in flow rate will cause a difference in release rate is an important basis for the subsequent calculation of the fluid production profile. Fig.12 It is the experimental result of the effect of flow rate on the slow-release performance of quantum dot tracer slow-release proppant.
[0078] It can be seen from the figure that there is no significant difference in the cumulative release concentration changes at the same time. The cumulative release concentration at a low flow rate is lower than that at a high flow rate, and the release rate at the initial stage of release at a high flow rate is faster than that at a low flow rate. As time goes by, the release rates at different flow rates eventually remain stable.
[0079] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0080] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A quantum dot tracer slow-release proppant and a preparation method thereof, characterized in that: The quantum dot tracer slow-release proppant is prepared by using ceramsite proppant, polymethacrylate and acetone as raw materials and adopting solvent evaporation method.
2. The quantum dot tracer slow-release proppant according to claim 1, characterized in that: The preparation method of the quantum dot tracer slow-release proppant comprises the following steps: S1: First, take a certain amount of silicon-based quantum dot tracer, add it to a certain amount of acetone solution and stir it thoroughly; S2: then adding polymethacrylate to the solution containing the acetone solution and the silicon-based quantum dot tracer, and continuing to stir until the polymethacrylate is completely dissolved; S3: adding a certain amount of ceramsite proppant into a mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer; S4: Then, the ceramsite proppant coated with the polymer solution in S3 is placed in a drying oven and evaporated for a period of time; S5: Finally, the dried ceramsite proppant is placed in a certain amount of deionized water, and the quantum dot slow-release proppant is obtained after ultrasonic dispersion for a period of time.
3. The method for preparing the quantum dot tracer slow-release proppant according to claim 2, characterized in that: In the step of taking a certain amount of silicon-based quantum dot tracer, adding it to a certain amount of acetone solution and stirring it thoroughly, 2 ml of silicon-based quantum dot tracer is taken and added to 4 ml of acetone solution and stirred thoroughly.
4. The method for preparing the quantum dot tracer slow-release proppant according to claim 2, characterized in that: In the step of adding polymethacrylate to the solution containing acetone solution and silicon-based quantum dot tracer, and continuing to stir until the polymethacrylate is completely dissolved, 1.2 ml of polymethacrylate is added to the solution containing acetone solution and silicon-based quantum dot tracer, and stirring is continued for 20 minutes until the polymethacrylate is completely dissolved.
5. The method for preparing the quantum dot tracer slow-release proppant according to claim 2, characterized in that: In the step of adding a certain amount of ceramsite proppant to a mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer, 10 g of ceramsite proppant is added to the mixed solution containing polymethacrylate, acetone solution and silicon-based quantum dot tracer.
6. The method for preparing the quantum dot tracer slow-release proppant according to claim 2, characterized in that: In the step of placing the ceramsite proppant wrapped by the polymer solution in S3 into a drying oven and evaporating for a period of time, the ceramsite proppant wrapped by the polymer solution is placed into a drying oven at 120° C. and evaporated for 2 hours.
7. The method for preparing the quantum dot tracer slow-release proppant according to claim 2, characterized in that: In the step of placing the dried ceramsite proppant in a certain amount of deionized water and ultrasonically dispersing it for a period of time to obtain the quantum dot slow-release proppant, the dried ceramsite proppant is placed in 50 ml of pure water and ultrasonically dispersed for 30 minutes to finally obtain the quantum dot slow-release proppant.